Development of zinc based alloy for solderability - Mustafa, Mohd. Yusry; Adesta, Erry Yulian Triblas; Purwanto, Hadi; Md. Azizan, Farihan (2011)
Zinc based alloy is being proposed as an alternative material in metal based giftware industry. Most of the giftware is handmade using simple process such as casting, polishing and soldering. Soldering of commercial zinc alloy is difficult due to poor bonding between solder material and base metal. Therefore, development of casting material is necessary to improve the solder properties. This work investigates the effect of aluminum and tin additions on the solder properties of zinc based alloy. Solder properties were studied based on the spread area and adhesion of molten solder alloy when it contacts the base metal. Experimental work was carried out by putting the base metal on an electrically heated aluminum block with the temperature set at 265°C. Solder alloy was first dipped in the flux solution and then transferred to the top of the base metal. The spread area values of the solidified solder alloy on the base metal were then estimated. Furthermore, scanning electron microscope (SEM) microstructure study and energy dispersive X-ray spectroscopy (EDX) elemental analysis were conducted. The results showed that tin addition has significant effect on the spread area compared to aluminum. Similarly, adhesions between base metal and solder alloy were positive for zinc alloyed with tin unlike zinc alloyed with aluminum.